Effects of pasteurization on the total phenolic content, radical scavenging activity, and physicochemical characteristics of sweet potato (Ipomea batatas) leaves and tips beverage - Binasoy, Joanne P.; Borazon, Elaine Q. (c2011.)
ABSTRACT This study aimed to determine the effects of different pasteurization temperatures (70, 80, and 90 °C) for 15 minutes on the physicochemical properties, TPC, and radical scavenging activity of sweet potato (Ipomea batatas) leaves and tips beverage. TPC was determined using the Folin- Ciocalteau Method. Antioxidant activity was measured based on the ability of the beverage to scavenge DPPH radical. Based from the results, Aw, L, a, and b values were not affected (p>0.05) by the different pasteurization temperatures. °Brix increased with increasing pasteurization temperature. TA increased significantly (p<0.05) for the beverage pasteurized at 90 °C. TPC increased with increasing pasteurization temperatures. The increase in TPC was responsible to the increase in the DPPH radical scavenging activity of the beverage as indicated by the high correlation (R2 = 0.835) between the TPC and EC50.
Thesis(BSFT)--University of the Philippines Diliman
Keywords: Sweet potatoes -- Processing; Beverages